Antigrowth and Apoptosis Inducing Effects of Hypericum Olympicum L. and Hypericum Adenotrichum Spach. on Lung Cancer Cells In Vitro: Involvement of DNA Damage. Issue 4 (8th February 2016) - Aztopal, Nazlihan; Erkisa, Merve; Celikler, Serap; Ulukaya, Engin; Ari, Ferda
Abstract: Hypericum species are used in different folk medicines and screened for their biological activity including cancer. We, therefore, evaluated the possible cytotoxic/apoptotic and genotoxic activities of Hypericum adenotrichum Spach. and Hypericum olympicum L. Antigrowth effect was screened in human lung cancer cell lines (A549 and PC3) by the ATP viability assay, while genotoxic activity was performed using the Comet assay. Histological and biochemical methods were utilized to elucidate the cell death mode. The results indicate that the crude methanol extracts of H. olympicum L. and H. adenotrichum have both antigrowth/cytotoxic and genotoxic activities on these cells in a dose dependent manner. These extracts clearly induced apoptosis in PC3 lung cancer cell lines. In this study, we report for the first time that the H. olympicum and H. adenotrichum exhibits potential cytotoxic and genotoxic activities in lung cancer cells as well as the apoptosis‐inducing roles through DNA damage in PC3 cells. Practical Applications: Medicinal plants are used in traditional medicine worldwide and several have been screened for their anticancer properties, we evaluated the possible cytotoxic and genotoxic activities of the Hypericum adenotrichum and Hypericum olympicum, which are still used in Turkish folk medicine. H. adenotrichum Spach., an endemic species in Turkey, and H. olympicum L., which are known as "kantaron" and used traditionally for their wound healing and antiseptic properties. It was found that Hypericum species showed a significant growth‐inhibiting effect on human lung cancer cells and induced apoptosis‐like cell death by DNA damage in PC3 lung cancer cells. These species may have a potential as anticancer agents and inspire to new improvements for medicinal chemistry.